2014
DOI: 10.1089/thy.2013.0460
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Serum Vitamin D3 Are Associated with Autoimmune Thyroid Disease in Pre-Menopausal Women

Abstract: Background: Low serum vitamin D levels have been associated with several autoimmune diseases, but their association with thyroid autoimmunity is unclear. We evaluated the association of serum vitamin D levels with the prevalence of autoimmune thyroid disease (AITD). Methods: Our cross-sectional study included subjects who underwent routine health checkups, which included assays of serum 25-hydroxy vitamin D3 [25(OH)D3] and anti-thyroid peroxidase antibody (TPO-Ab), as well as thyroid ultrasonography (US) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 34 publications
(48 reference statements)
4
69
2
2
Order By: Relevance
“…6 Other studies also showed lower serum 25(OH)D levels or a higher prevalence of vitamin D insufficiency in AITD or HT 9,10 and a negative correlation between 25(OH) D and TPO-Ab levels in AITD or HT. 9,14,22 In a recent Chinese population-based health survey, a negative correlation was found between 25(OH)D levels and Tg-Ab levels in female individuals. 23 Additionally, a few studies have reported an inverse relationship between 25(OH)D and TSH levels or severity in HT, as in the present study, suggesting the association between low vitamin D status and progressive thyrocyte damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Other studies also showed lower serum 25(OH)D levels or a higher prevalence of vitamin D insufficiency in AITD or HT 9,10 and a negative correlation between 25(OH) D and TPO-Ab levels in AITD or HT. 9,14,22 In a recent Chinese population-based health survey, a negative correlation was found between 25(OH)D levels and Tg-Ab levels in female individuals. 23 Additionally, a few studies have reported an inverse relationship between 25(OH)D and TSH levels or severity in HT, as in the present study, suggesting the association between low vitamin D status and progressive thyrocyte damage.…”
Section: Discussionmentioning
confidence: 99%
“…25 The present study reported a relatively high mean vitamin D level and low prevalence of vitamin D insufficiency and deficiency compared to other Korean population-based studies. 22,30 One of the Korean studies reported that the mean serum level of 25(OH)D was 52.9 nmol/L (21.2 ng/mL) in males (aged 10-91 years) and 45.4 nmol/L (18.2 ng/mL) in females ranging in age from 10-93 years, while vitamin D insufficiency/deficiency was found in 86.8%/47.3% of males and 93.3%/64.5% of females by the Fourth Korea National Health and Nutrition Examination Surveys in the Korean population in 2008. 30 In the current study, adult patients who visited a tertiary hospital for thyroid evaluation or follow-up were enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described (16), serum TSH levels were measured using the TSH-CTK-3a radioimmunoassay (RIA; DiaSorin SpA, Saluggia, Italy) with a functional sensitivity of 0.07 mIU/L. Serum fT4 levels were determined using the fT4 RIA (Immunotech, Prague, Czech Republic).…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Hypovitaminosis D and thyroid autoimmunity were also described in a Chinese female population, where decreased TPOAb levels were associated with higher vitamin D levels. Interestingly, the correlation was found only in premenopausal women, but not in postmenopausal women or in men [4]. This result suggests a likely involvement of estrogens in modulating AITD.…”
Section: (Oh)d Values Than Healthy Controls (P =mentioning
confidence: 80%